2012
DOI: 10.1002/pits.21647
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Clinical Trial Replication of a Psychosocial Treatment for Children with High‐Functioning Autism Spectrum Disorders

Abstract: This replication randomized clinical trial examined the efficacy of a comprehensive psychosocial intervention for children aged 7 to 12 years with high‐functioning autism spectrum disorders (HFASDs). Participants were randomly assigned to treatment or wait‐list conditions. Treatment included instruction and therapeutic activities targeting social skills, face‐emotion recognition, interest expansion, and interpretation of non‐literal language. A response‐cost program was used to reduce problem behaviors and inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
37
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 27 publications
5
37
1
Order By: Relevance
“…These fidelity and satisfaction ratings were consistent with prior studies of summerMAX (Lopata et al, 2010;Thomeer et al, 2012) and suggested that reducing treatment intensity did not affect program feasibility. For staff clinicians, this finding was particularly important as staff effort toward accurate treatment implementation can be affected by their perception of the protocol (Bellini, Peters, Benner, & Hopf, 2007).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…These fidelity and satisfaction ratings were consistent with prior studies of summerMAX (Lopata et al, 2010;Thomeer et al, 2012) and suggested that reducing treatment intensity did not affect program feasibility. For staff clinicians, this finding was particularly important as staff effort toward accurate treatment implementation can be affected by their perception of the protocol (Bellini, Peters, Benner, & Hopf, 2007).…”
Section: Discussionsupporting
confidence: 88%
“…The lack of significant improvement on the DANVA-2 Child Faces test is similar to the previous RCTs of the summerMAX program. The inconsistent and weak effects on the DANVA-2 in this and prior studies of the summerMAX program (Lopata et al, 2008(Lopata et al, , 2010Thomeer et al, 2012) may indicate poor measure sensitivity or a reduced treatment effect on decoding skills. Ongoing research may benefit from examination of alternate measures of decoding skills and/or a modification of the face-emotion decoding treatment component of the Standards for v 2 : small = .01, medium = .08, and large = .18 (Cumming, 2012).…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…are used to increase skills acquisition and reduce ASD symptoms and behavior problems, and weekly parent training is provided (see Section 2.3). Five studies have evaluated the efficacy of the program including two RCTs (for a summary of the treatment trials, see Lopata et al, 2013 also Thomeer et al, 2012). These studies have consistently found the treatment produced significant gains in the children's social cognition (i.e., knowledge of social responses and component steps for targeted skills) and understanding of non-literal language, and in parent and staff ratings of targeted social skills, ASD symptoms, and broader social skills.…”
Section: Introductionmentioning
confidence: 99%
“…Our search identified two additional trials of comparable interventions (52,53), which were published after the final search in the review by Reichow and colleagues (11). In a trial from the United States (52), a total of 35 children were randomized to social skills group training or to being waitlisted.…”
Section: Social Skills Trainingmentioning
confidence: 99%